PERILAKU MENGHISAP LEM PADA ANAK REMAJA (STUDI KASUS DI KOTA PEKANBARU) - Siti Chomariah; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Teens are the age group most susceptible since adolescence is a time from childhood into adulthood causing them to fall into behavior "ngelem”. This research aims to find out what are the factors the causes of teenagers calculate glue. This study is a qualitative study with technique of collecting data obtained in the study through the in-depth interviews and observations to 8 respondent. The unit of analysis is the study of teens calculate of glue. Respondent in the study were young men aged 15-21 years who are addicted calculate of glue. The results showed that the factors encouraging teens start behavior calculate of glue namely family, peers and the influence of the environment. This study suggests counseling should be done about the impact of behavior calculate of glue through institutions and schools, Expected to parents (families) to direct their children in choosing friends hanging out right.Keywords: Behavior, teens, External Factors